马来西亚青年华人的詈言使用 = The use of swear words by young Malaysian Chinese - 黄顺铭 Ng, Soon Ming (Nanyang Technological University, 2021)
马来西亚的社会由多元种族构成，也因此形成了多重语言的环境。大多数的马来西亚华人虽以华语作为母语，但也能掌握其他语言，如：马来语、英语、其他汉方言等。在如此环境之下，他们使用詈言时所表现的语言特点必然也有研究价值。本文旨在调查马来西亚青年华人在不同场合下，使用詈言时的语言选择情况。结果显示，受试者对于詈言的语言选择大致上与他们对于该语言的掌握度及使用程度趋势相符。华语詈言占了大部分，其后为英语、福建和粤语詈言。其中华语和福建詈言多使用于宣泄负面情绪的场合；英语和粤语詈言则多使用于正面情绪的场合。虽然马来语的掌握度和使用度都与英语接近，但受试者却极少使用马来语詈言。 Malaysia is a multicultural country, and this led to a multilingual society. Although majority of the Chinese in Malaysia have Mandarin as their mother tongue, they are also proficient in other languages such as Malay, English, and other Chinese dialects. Hence, it is worthwhile to investigate in the linguistic features that Malaysian Chinese exhibit while using swear words. This study focuses on investigating the language choices made by young Malaysian Chinese when they are swearing under different circumstances. Results show that participants tend to use the language which they are proficient with when they swear. The amount of swear words reported in Mandarin was the highest, followed by English, Hokkien and Cantonese. Mandarin and Hokkien swear words were used mostly to express negative emotion. In contrast, English and Cantonese swear words were used mostly to express positive emotion. Even though the participants had similar proficiency in Malay and English, they are unlikely to use Malay swear words in either circumstances.